Rękopiśmienne wierszowane litteraria od średniowiecza do końca XVIII wieku w zbiorach benedyktynek sandomierskich. Część druga: winszujące kolędy klasztorne dla ksieni Marianny Siemianowskiej - Trościński, Grzegorz (Tematy i Konteksty, 2016)
The article describes the collection of carols which were written in the Benedictine convent in Sandomierz in the latter half of the 18th century. They belong to the type of congratulatory carols and were dedicated to Prioress Marianna Siemianowska on the occasion of subsequent jubilees of her office as prioress of the Benedictines in Sandomierz. They are preserved in manuscript in Diocesan Library in Sandomierz. They are an interesting contribution to the history of convent folklore and research into the customs of the Benedictine Order in Sandomierz. The pieces centre upon two fundamental themes: firstly, the birth of Christ, and, secondly, creation of the panegyric image of the prioress as well as wishes on the occasion of Christmas and the jubilee.